2018
DOI: 10.1136/bmjgast-2018-000253
|View full text |Cite
|
Sign up to set email alerts
|

Adenoma Detection before and after the age of 50: a retrospective analysis of Lebanese outpatients

Abstract: Background and aimColorectal cancer (CRC) has an increased impact on the Lebanese population’s morbidity and mortality. This study evaluated the situation of adenoma detection in an outpatient clinic in Lebanon.Patients and methods918 patients underwent colonoscopy over a period of 24 months by a qualified physician. Biopsy results were divided into normal versus abnormal colonic tissue, which was further subdivided into number of polyps and cancer.ResultsOut of 918 individuals included, 82 cases of Crohn’s co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…Regarding age, many studies have reported the association between age and colorectal polyps [ 29 , 30 ], suggesting that CRC screening should be performed around the age of 50–60 years in the general population owing to >80% of CRCs being diagnosed over the age of 60 years, which is consistent with our results [ 31 , 32 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding age, many studies have reported the association between age and colorectal polyps [ 29 , 30 ], suggesting that CRC screening should be performed around the age of 50–60 years in the general population owing to >80% of CRCs being diagnosed over the age of 60 years, which is consistent with our results [ 31 , 32 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
“… 28 Similarly, an increasing incidence of CRC and adenomatous polyps in younger age groups has been reported in international studies. 29 , 30 , 31 As with other studies, we found no association between gender and adenomatous polyps. 14 , 16 …”
Section: Discussionsupporting
confidence: 89%
“…20-26, 28-32, 34, 35, 41-43, 45, 46 . Of the 19 studies of patients undergoing colonoscopy, 7 studies were performed on symptomatic patients alone 20,21,23,30,32,41,43 , 6 on asymptomatic patients 22,28,31,34,43,47 , and 6 did not specify whether patients were symptomatic or not 24,26,29,35,42,45 . The time period for assessment of our outcome data ranged from 1972 to 2017, with 19 of them conducted in patients undergoing colonoscopy after the year 1995, 3 studies prior to 1995, and 2 that began prior to 1995, but continued past this time.…”
Section: Literature Reviewmentioning
confidence: 99%